2009
DOI: 10.3766/jaaa.20.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Distress, Anxiety, Depression, and Hearing Problems among Cochlear Implant Patients with Tinnitus

Abstract: Tinnitus can be a significant problem following CI, but that the experienced distress is often moderate. However, a quarter of CI recipients do demonstrate moderate/severe tinnitus handicap, and thus are candidates for tinnitus specific therapy. The level of tinnitus handicap is associated with hearing problems and psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
71
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 23 publications
12
71
2
Order By: Relevance
“…The present results suggest that CI users may experience a relief in tinnitus persistence, but not a complete abolition of tinnitus or tinnitus-related distress. Studies investigating other aspects of tinnitus handicap in CI users are encouraging (e.g., anxiety and depression; Andersson et al 2009;Olze et al 2011;Kloostra et al 2015), but a more comprehensive characterization of tinnitus symptoms is still needed to understand the burden of tinnitus after cochlear implantation. It is only through such understanding that appropriate interventions for alleviating the burden of tinnitus in implant users can be identified and developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results suggest that CI users may experience a relief in tinnitus persistence, but not a complete abolition of tinnitus or tinnitus-related distress. Studies investigating other aspects of tinnitus handicap in CI users are encouraging (e.g., anxiety and depression; Andersson et al 2009;Olze et al 2011;Kloostra et al 2015), but a more comprehensive characterization of tinnitus symptoms is still needed to understand the burden of tinnitus after cochlear implantation. It is only through such understanding that appropriate interventions for alleviating the burden of tinnitus in implant users can be identified and developed.…”
Section: Discussionmentioning
confidence: 99%
“…If one assumes reporting moderately or severely distressing tinnitus as "significant" enough to consider additional tinnitus management options after implantation (Andersson et al 2009), the estimate of 37% of CI users found in the present study (Table 3) would be somewhat higher than the 25% of "clinically significant" tinnitus estimated from data reported in other studies (Baguley 2010). If one also assumes that the candidate group was representative of those who are eligible to receive a CI in the UK, then the proportion of patients reporting current tinnitus of any kind (56%) was lower than the average estimate of 80% in CI candidates (lower limit of 67%) extrapolated from results of a number of studies (Baguley & Atlas 2007).…”
Section: Tinnitus Before and After Implantationmentioning
confidence: 99%
“…On the other hand, following CI, these patients may be treated with specific fitting of the implant and/or tinnitus therapy. Andersson et al [2009] also reported a correlation between tinnitus distress and anxiety or depression but analyzed the data after and not before CI.…”
Section: Discussionmentioning
confidence: 99%
“…Because our patients were deaf before the CI surgery, changes in frequency and intensity of tinnitus could not be evaluated. Some previous studies used validated questionnaires to assess the tinnitus handicap in the implanted patients [Andersson et al, 2009;Miyamoto et al, 1997;Pan et al, 2009;Quaranta et al, 2008;Souliere Jr. et al, 1992]. However, data regarding tinnitus impairment before and after CI often include general information: better, no change or worse [Mo et al, 2002;Tyler, 1994].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation